Multiobjective optimization of an air-phase change material heat exchanger for free cooling in a single-family house. (December 2020) - Rouault, Fabien; Bruneau, Denis; Sebastian, Patrick; Lopez, Jérome
Highlights: We propose a 1D model of the storage device transferring heat into air during the charge and discharge phases. We show a comparison between experimental results and simulation results. We propose a method of multi objective optimization which take into account fan energy use, PCM initial cost and number of thermal discomfort as design objectives. A set of optimized systems is proposed according to different optimization strategies. Abstract: Free cooling systems based on phase change materials (PCM) are a possible alternative to air conditioning systems for summer comfort in buildings. However, the performance of such cooling systems is closely related to the climatic conditions and building configurations to be cooled. The objective of this work is to present an application of multiobjective optimization of an air cooling system using PCM at the preliminary stage of the design process. A dynamic thermal model simulating the thermal behaviour of an air-PCM heat exchanger is therefore presented and then coupled to the EnergyPlus Ⓡ software for the dynamic thermal simulation of the system. Finally, a first application of the optimization is presented to define a set of optimal configurations of the systems maintaining summer comfort in the house NAPEVOMO, minimizing both the initial cost of PCM and energy use of the fan.